Learning of intercultural competences and languages at school and their influence on global competences and immigrant-origin peers’ sense of belonging - Alisaari Jenni; Kilpi-Jakonen Elina (Jyväskylän yliopisto, 2023)
In this study, we use PISA 2018 data to analyze (1) how language learning and teaching of intercultural issues are associated with global competences (GC) both in terms of knowledge and skills aspects as well as attitudes towards diversity, (2a) how the teaching of languages and intercultural issues in the school are related to sense of belonging among young people with migration backgrounds, and (2b) how peers’ global knowledge and skills as well as attitudes are related to migrant origin students’ sense of belonging at school. Aspects of global competences related to attitudes and cognitive skills are investigated separately. The teaching of intercultural competences was found to be positively associated with the four attitudinal aspects of global competences but negatively associated with the knowledge and cognitive skills associated with GC. Students studying two (or more) world languages tended to display more negative attitudes than those studying just one, in particular for respect for people from other cultures. Furthermore, learning two (or more) world languages versus one also tended to be associated with lower knowledge and cognitive skills related to GC. At the school-level the teaching of intercultural competences or languages were not associated with the sense of belonging of children of immigrants. Peers’ attitudes, in particular their awareness of intercultural communication, were more strongly associated with children of immigrants’ sense of belonging than their peers’ cognitive competences. Thus, we argue that the measurement of global knowledge and skills may be in need of critical reconsideration. Furthermore, it would be beneficial to define more explicitly, which aspects are related to effective intercultural training.